2019
DOI: 10.3847/2041-8213/ab38c3
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Near-infrared Brightness and Variability of Sgr A*

Abstract: The electromagnetic counterpart to the Galactic center supermassive black hole, Sgr A*, has been observed in the near-infrared for over 20 years and is known to be highly variable. We report new Keck Telescope observations showing that Sgr A* reached much brighter flux levels in 2019 than ever measured at near-infrared wavelengths. In the K band, Sgr A* reached flux levels of ∼ 6 mJy, twice the level of the previously observed peak flux from > 13, 000 measurements over 130 nights with the VLT and Keck Telescop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 60 publications
6
115
0
3
Order By: Relevance
“…The recent closest approach of S0-2 has been used to test and confirm the prediction of general relativity for the relativistic redshift (e.g., GRAVITY Collaboration et al 2018;Do et al 2019a). This well-studied star provides an opportunity to place limits on the inner orbit's configuration.…”
Section: The Time Variability Of a Stellar Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent closest approach of S0-2 has been used to test and confirm the prediction of general relativity for the relativistic redshift (e.g., GRAVITY Collaboration et al 2018;Do et al 2019a). This well-studied star provides an opportunity to place limits on the inner orbit's configuration.…”
Section: The Time Variability Of a Stellar Orbitmentioning
confidence: 99%
“…These orbits imply the presence of a 4 million solar masses black hole (e.g., Ghez et al 2000Ghez et al , 2008Gillessen et al 2009;Boehle et al 2016;Gillessen et al 2017;Gravity Collaboration et al 2019), residing in a dense stellar environment, called a nuclear star cluster (e.g., Ghez et al 2003;Gillessen et al 2009;Lu et al 2013). Continued observations have enabled precision measurements of the distance to the galactic center (e.g.. Ghez et al 2003;Boehle et al 2016;Gravity Collaboration et al 2019), new constrains on the fifth force (Hees et al 2017a) and the first gravitational redshift measurements near a SMBH (GRAV-ITY Collaboration et al 2018;Do et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…On May 2019, Do et al (2019) observed an unprecedented NIR flare from Sgr A * -hereafter the "superflare"-with the Keck telescope. The peak flux exceeded the maximum historical value by a factor of two and the light curve (LC) afterwards showed a factor of 75 drop in flux over a 2 hr time span.…”
Section: Introductionmentioning
confidence: 99%
“…The peak flux exceeded the maximum historical value by a factor of two and the light curve (LC) afterwards showed a factor of 75 drop in flux over a 2 hr time span. Do et al (2019) suggested that an increase in the SMBH accretion ratė M could be responsible for the superflare, possibly due to additional gas deposited by the passage of the G2 object in 2014 or a windy star such as S0-2 in 2018. Nevertheless, Ressler et al (2018) argued that the effect of S0-2 on the RIAF structure should be negligible.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in flaring rate of the most energetic fares must be placed in the context of the recent increase in activity observed from Sgr A* in NIR and X-rays. Do et al (2019) observed the Galactic center with the Very Large Telescope (VLT) and the Keck Telescope in 2019 April and May. They recorded the highest variability ever observed over 20 years of NIR observations (up to a factor of 75 within two hours).…”
Section: Discussionmentioning
confidence: 99%